Performance Evaluation of Physically and Chemically Modified Pumice on Removal of Cu(II) from Aqueous Solution - Indah, Shinta; Helard, Denny; Primasari, Budhi; Edwin, Tivany; Andeslin, Sarah (Trends in Sciences, 2022)
Modification by physical and chemical treatments was evaluated to increase the adsorption capability of natural pumice in the removal of Cu(II) from aqueous solution. The treatments were heating at temperatures of 300, 450 and 600 ℃ for physical and soaking in acid solutions (HCl, H2SO4 and HNO3) for chemical treatment. The adsorption was performed in the batch system at the optimum condition (5 of pH solution, < 63 µm of adsorbent diameter, 3 g/L of adsorbent dose, 5 mg/L of Cu(II) concentration and 30 min of contact time). The results showed the removal efficiency and Cu(II) uptake increased using modified pumice from 71.19 % and 1.19 mg/g to 84.45 % and 1.41 mg/g. The highest removal efficiency and Cu(II) uptake were obtained from 300℃ of heating temperature and HCl for the acid solution. The application of physical and chemical treatments in modification has the potential to increase the removal efficiency and heavy metal uptake of the natural pumice. HIGHLIGHTS Various methods have been evaluated for the modification of pumice to improve their sorption capacity Physical and chemical treatment to pumice may modify the surface areas, pore structures, and chemical functional group on the surface of the pumice GRAPHICAL ABSTRACT